The Use of Reduction Rhinoplasty to Accommodate a Local Flap for Large Nasal Tip Defect Reconstruction - Linda Regina Gudjonsdottir, BMsc; Gudjon Leifur Gunnarsson, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. A nasal tip defect can pose a reconstructive challenge, especially if the defect size overrides the availability of a local flap for coverage. We decreased the size of the nasal tip and lifted it to accommodate a local flap reconstruction of a smaller nose. We present a case series of 7 patients 65–95 years of age who underwent removal of a nasal tip lesion involving the whole aesthetic unit of the nasal tip, to demonstrate the technique on noses of different sizes and shapes, with nasal tip reduction and local flap coverage. The operation and recovery were uneventful, and reconstructive goals were achieved without any complications in a single stage with overall satisfactory results. The local flaps of the nose allow for wide exposure of the underlying nasal support. Reduction of the alar cartilage and slight lift of the nasal tip narrows the soft-tissue defect sufficiently and allows for a simple local flap reconstruction.